Carleman estimates for coefficient inverse problems and numerical applications - Klibanov, M. V. (Michael V.) (Inverse and ill-posed problems series., 2004)
In this monograph, the main subject of the author's considerations is coefficient inverse problems. Arising in many areas of natural sciences and technology, such problems consist of determining the variable coefficients of a certain differential operator defined in a domain from boundary measurements of a solution or its functionals. Although the authors pay strong attention to the rigorous justification of known results, they place the primary emphasis on new concepts and developments.